Status Kebersihan Gigi dan Mulut dengan Status Karies Gigi (Kajian pada Murid Kelompok Umur 12 Tahun di Sekolah Dasar Negeri Kota Bukittinggi) - Syukra Alhamda (Fakultas Kedokteran Universitas Gadjah Mada, 2011)
Dental and Oral Hygiene Status with Dental Caries Status(Study in Student Age Group 12 Years in Elementary School City of Bukittinggi)Background: Teeth and mouth disease has the first ranked at 77% of the population disease prevalence of 10 complained of by the community. Dental caries in 12th aged group ends to increase from year to year. In general teeth and mouth disease that affect many people of Indonesia relating to oral hygiene. According to expert opinion one of the factors that are directly related to the occurrence of caries is oral hygiene. The purpose of this study was to correlate the status of oral hygiene with dental caries status.Method: This study used Cross-sectional design and conducted in elementary school city of Bukittinggi. The subjects were all students in 12th aged group which are permanent teeths all. Measuring tools used is the OHI-S (Oral Hygiene Index-Simplified) for dental and oral hygiene status, and Decay Missing Filling (DMF)- index for dental caries status with the analysis Pearson’s correlation test and simple linear regression based on significance level at 0.05.Result: Oral and hygiene status of the students in 12th aged group elementary school city of Bukittinggi is in goodcategory, with the high caries prevalence 55,68% and the average of DMF-T 1.35. Statical analysis showed a significant and positive relationship between status of oral hygiene with dental caries status as the indicated by the value of ß = 0.685 and p = 0.01. The result also showed that the mean DMF-T of female students is higher than male students indicated by the value of p = 0.00 < 0.05.Conclusions: The better oral hygiene status of the students the better also the status of dental caries.Keywords: oral hygiene and dental caries, DMFT (Dental, Missing, Filling-Teeth), dental caries, Oral Hygiene Index Simplified (OHI-S)